Environmental cleanup at Navy facilities : adaptive site management - National Research Council (U.S.). Committee on Environmental Remediation at Naval Facilities (Washington, D.C. : National Academies Press, 2003)
The number of hazardous waste sites across the United States has grown to approximately 217,000, with billions of cubic yards of soil, sediment, and groundwater plumes requiring remediation. Sites contaminated with recalcitrant contaminants or with complex hydrogeological features have proved to be a significant challenge to cleanup on every level--technologically, financially, legally, and sociopolitically. Like many federal agencies, the Navy is a responsible party with a large liability in hazardous waste sites. "Environmental Cleanup at Navy Facilities applies the concepts of adaptive management to complex, high-risk hazardous waste sites that are typical of the military, EPA, and other responsible parties. The report suggests ways to make forward progress at sites with recalcitrant contamination that have stalled prior to meeting cleanup goals. This encompasses more rigorous data collection and analysis, consideration of alternative treatment technologies, and comprehensive long-term stewardship
Front Matter -- Contents -- Preface -- SUMMARY -- 1 INTRODUCTION -- 2 ADAPTIVE SITE MANAGEMENT -- 3 MONITORING AND DATA ANALYSIS TO SUPPORT ADAPTIVE SITE MANAGEMENT -- 4 EVALUATION AND EXPERIMENTATION -- 5 TECHNOLOGY OVERVIEW -- 6 NONTECHNICAL ISSUES REGARDING THE USE OF ADAPTIVE SITE MANAGEMENT -- Appendixes -- A ACRONYMS -- B REMEDIATION CASE STUDIES -- C TABLES OF INNOVATIVE TECHNOLOGY DEMONSTRATION PROJECTS -- D COMMITTEE MEMBER AND STAFF BIOGRAPHIES
"Support for this project was provided by the U.S. Navy under Contract No. N47408-00-C-7102"--Title page verso
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: United States. -- Navy -- Facilities -- Environmental aspects; United States. -- Navy; Navy-yards and naval stations -- Environmental aspects -- United States; Hazardous waste site remediation -- United States; Hazardous waste sites -- United States -- Management; Bases navales -- Aspect de l'environnement -- États-Unis.; Dépôts de déchets dangereux -- Restauration -- États-Unis.; Dépôts de déchets dangereux -- États-Unis -- Gestion; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; Armed Forces -- Facilities -- Environmental aspects; Hazardous waste site remediation; Hazardous waste sites -- Management; Navy-yards and naval stations -- Environmental aspects; United States